Rainfall Characteristics and Incidence of Meteorological Droughts in Sirohi District of Rajasthan - Rao, A S; Poonia, Surendra; Singh, D V (Annals of Arid Zone, 2016)
The rainfall characteristics and meteorological drought conditions in Sirohi District of Rajasthan were studied by analyzing the rainfall data (1901-2012) of three tehsils namely Reodar, Sirohi and Sheoganj. Three tehsils experience 520 to 621 mm of average annual rainfall in 24 to 27 days, out of which 482 to 580 mm occurs during June to September. The lowest annual rainfall in Sirohi was 140 mm in 1901 and highest of 1578 mm in 1973, whereas at Sheoganj, it varied from 157 mm in 1918 to 1689 mm in 1973 mm and at Reodar from 54 mm in 1987 to 1495 mm in 1973. The 1-day rainfall for return periods of 5, 10, 25, 50 and 100 years was 139.1, 168.8, 205.8, 233.4 and 261.6 mm at Sheoganj, 156.1, 192.7, 238.3, 272.3 and 307.0 mm at Reodar and 169.7, 209.5, 259.0, 296.0 and 333.7 mm at Sirohi. The long-term annual rainfall trends showed that there was an increase at a rate 0.62 mm year-1 at Sirohi, 0.24 mm year-1 at Sheoganj and 0.85 mm year-1 at Reodar. The severe meteorological droughts occurred in 11-12% years at Sirohi and Sheoganj and in 19% years at Reodar, whereas, mild drought in 23-29% and moderate drought in 19% years at all the locations. Key words: Rainfall characteristics, meteorological drought, Sirohi District.